Bibliometric Analysis of Research on Cosmetic Products: Halal Cosmetics as an Emerging Research Area - Nurul Izzati Bahrin; Nur Sa’adah Muhamad; Khairul Akmaliah Adham; Alina Abdul Rahim; Azreen Jihan Che Mohd Hashim (IIUM Press, 2024)
The cosmetics industry is one of the most lucrative and high-growing industries that are driven by science and innovation. However, there is a lack of studies that analyze scholarly articles on cosmetic products. This study attempts to bridge this gap by reviewing the existing literature, with the specific purpose to explore the trends in the publications and themes related to research on cosmetic products. To achieve this purpose, a bibliometric analysis was conducted using the R application and R-based tools. The research retrieved 613 articles on the Scopus database that used the term ‘cosmetic products’ in their titles. The study reveals that the number of articles published on the topic of cosmetic products is increasing. Two main keywords, paraben, and high-performance liquid chromatography, are the most recurring themes. Halal cosmetics were identified as an emerging research area. In relation to this context, six major topics were identified, which are: regulations for halal certification of halal cosmetics, organization control, attributes of halal cosmetics, consumer purchase, and purchase intention. Overall, this bibliometric analysis provides essential information on the current trends and themes, and provides recommendations for future research on cosmetic products.